Drystone Walls: Interface between geological and cultural heritage? - Rosendahl, Stefan (2022)
The aim of this work is to show the existence of interfaces between various types of heritage and the benfits of these heritage's crossing. Qualitative non-interventionist methodologies were used, and bibliographic, cartographic, and field visits were carried out. Visits guided by the authors and discussions with specialists and non-specialists were a priceless support of the realization of the study. The interaction with the local population was an important part of the methodology to understand the territories in question. The deductive method was also used.